The Effect of Product Quality and Brand Love on Repurchase Intention on Apple Brand (Study on Generation Z Students Using Apple Products at the University of North Sumatra) - Giovandhi, Leonardo; Adlina, Hafiza (Journal of Economics and Business (JECOMBI), 2023)
The lack of understanding the concept of product quality and customer love for the brand made Apple loyal consumers and especially Generation Z who like to try new things, choose to try using products from other brands on the market. This study aims to analyze the effect of product quality on repurchase intention on Apple brand among students of Generation Z University of North Sumatera, analyze the effect of brand love on repurchase intention on Apple brand among students of Generation Z University of North Sumatera, and to analyze the effect of product quality and brand love on repurchase intention on Apple brand among students of Generation Z University of North Sumatera. The form of research used in this study is quantitative research with associative approach. Sampling is done through probability sampling technique and using 100 respondents as a sample. Data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis test. The results showed that Product Quality significantly affect Repurchase Intention. Meanwhile, the Brand Love variable has a significant effect on Repurchase Intention. Product Quality and Brand Love also affect together the dependent variable is Repurchase Intention .